Health and Economic Burden of Preeclampsia: No Time for Complacency. Issue 2 (June 2018) - Li, R.; Tsigas, E.Z.; Callaghan, W.M.
Abstract : ( Am J Obstet Gynecol . 2017;217(3):235–236) Over the past 30 years, the incidence of preeclampsia has increased. Preeclampsia can have adverse health consequences. Stevens et al found the short-term costs of preeclampsia in the United States health care system in 2012 was $2.18 billion. In their report, administrative data were used to identify preeclampsia and other complications. As a result of using administrative databases, some causes of mild preeclampsia may have been inaccurately coded or misdiagnosed. In order to compute costs, novel approaches were used, but such approaches should be validated. As a leading cause of both maternal and fetal complications, preeclampsia has not received the attention or research it deserves. By quantifying the costs, the public as well as health care professionals can better gauge the scope of the complication. Further study should explore the costs of intervention and cost savings associated with preventing preeclampsia, as well as long-term costs of preeclampsia.